2017
DOI: 10.1002/esp.4076
|View full text |Cite
|
Sign up to set email alerts
|

Physical environmental controls on riparian root profiles associated with black poplar (Populus nigra L.) along the Tagliamento River, Italy

Abstract: Tree roots contribute to the resistance of riparian sediments to physical deformation and disintegration. Understanding reinforcement by roots requires information on root distributions within riparian soils and sediments. Continuous‐depth models or curves have been proposed to describe vertical root density variations, providing useful indicators of the types of function that may be appropriate to riparian trees, but have generally been estimated for terrestrial species or broad vegetation types rather than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Figure 1, 2002 image shows sprouting trees deposited in 2000). In nearly all cases, the deposited trees that initiate pioneer islands in the study reach are black poplar (P. nigra), a facultative phreatophyte capable of rapid root growth in response to different water and sediment conditions (Holloway et al, 2017a(Holloway et al, , 2017b(Holloway et al, , 2017c, and the LiDAR data and field measurements show that deposited trees of this species can regenerate to produce a canopy that grows rapidly, particularly in the first 15 years following deposition ( Figure 6A). The median canopy height increased from 0.24 to 6.85 m (6.61 m growth) on the 2004PI surfaces, from 1.64 to 9.76 m (8.72 m growth) on the 2000PI surfaces and from 22.79 to 25.04 m (2.83 m growth) on the 1980EI surfaces between 2005 and 2013.…”
Section: Evolution Of Islands Over Years To Decadesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1, 2002 image shows sprouting trees deposited in 2000). In nearly all cases, the deposited trees that initiate pioneer islands in the study reach are black poplar (P. nigra), a facultative phreatophyte capable of rapid root growth in response to different water and sediment conditions (Holloway et al, 2017a(Holloway et al, , 2017b(Holloway et al, , 2017c, and the LiDAR data and field measurements show that deposited trees of this species can regenerate to produce a canopy that grows rapidly, particularly in the first 15 years following deposition ( Figure 6A). The median canopy height increased from 0.24 to 6.85 m (6.61 m growth) on the 2004PI surfaces, from 1.64 to 9.76 m (8.72 m growth) on the 2000PI surfaces and from 22.79 to 25.04 m (2.83 m growth) on the 1980EI surfaces between 2005 and 2013.…”
Section: Evolution Of Islands Over Years To Decadesmentioning
confidence: 99%
“…capable of resprouting) on bar surfaces during the falling limb of flood events, through an initial pioneer island phase of sprouting and sediment retention, to an established island phase as a result of the aggradation, enlargement and coalescence of pioneer islands. Since 2001, a number of refinements to the conceptual model have been introduced (Gurnell and Petts, ; Gurnell et al, , ), and empirical evidence has been presented to support specific aspects of the model, including for example, island morphological (Bertoldi et al, ), sedimentological (Gurnell et al ., ), soil (Mardhiah et al, ; Bätz et al, ), and vegetation development (Francis et al, ; Perona et al, ); living wood recruitment and dynamics (Bertoldi et al, ); early growth rates of tree seedlings, cuttings and deposited trees (Francis et al, ; Francis et al, ; Francis and Gurnell, ; Francis, ; Moggridge and Gurnell, ) and interactions among developing subsurface tree root and shoot biomass and sediment retention (Holloway et al, , , ). In this paper we integrate empirical evidence of the processes and forms that accompany island evolution over decadal to event timescales, focusing on a single island‐braided reach of the Tagliamento River, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Aggradation around vegetation of 0.5 m in the first 5 years of growth and 1.5 – 2 m over 25 years has been observed in the study reach (Gurnell et al, 2019). Hortobágyi et al (2018), following Eichel, Corenblit, & Dikau (2015), have described such periods of landform building as “biogeomorphic feedback windows”, providing trees with elevational protection from floods and finer, moisture‐retentive sediments within which to develop extensive root systems (Holloway et al, 2017; Holloway, Rillig, & Gurnell, 2017a, 2017b). Furthermore, the numerous flow pulses between the 2008 and 2012 floods likely provided opportunities for further sediment trapping as the surviving trees matured, providing an increasing potential for them to survive the 2012 event.…”
Section: Discussionmentioning
confidence: 99%
“…Building on knowledge of life history and ecological characteristics (Karrenberg, Edwards, & Kollmann, 2002), much research has focused on the role of Salicaceae species in initiating, building and sustaining landforms (Corenblit et al, 2009; Francis, Corenblit, & Edwards, 2009; Gurnell, Tockner, Edwards, & Petts, 2005) and thus creating a topographic signature of vegetation development across river beds and margins (Bertoldi, Gurnell, & Drake, 2011; Bywater‐Reyes, Wilcox, & Diehl, 2017). Research has also revealed the biomechanical properties of the Salicaceae that allow this family to survive, to retain fluvial sediments and to build and reinforce landforms (e.g., Imada, Yamanaka, & Tamai, 2008; Scippa, Trupiano, Rocco, Di Iorio, & Chiatante, 2008; Pasquale, Perona, Francis, & Burlando, 2012; Bankhead, Thomas, & Simon, 2017; Holloway, Rillig, & Gurnell, 2017; Holloway et al, 2017a, 2017b; Wintenberger, Rodrigues, Juge, & Villar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Each reach was approximately 2 km in length and the reaches were spaced approximately 4 km and 28 km apart. Previous research has separated these nine sites into two distinct groups – wet and dry sites – according to soil moisture conditions (Holloway et al, ) and has shown distinct differences in the vertical profiles of root density and root area ratio according to whether data were collected at the wet or dry sites. However, no significant difference was found in the relationship between root tensile strength and diameter according to moisture conditions, suggesting that root tensile strength is insensitive to this environmental property, despite the fact that root profiles show distinct differences.…”
Section: Data Sets Analysedmentioning
confidence: 99%